White Girls and the "Other" in the New Latino Diaspora: The Conflation of Deviance and Immigration and the Role of Language. - Sierk, Jessica (Theory in Action, 2019)
Throughout his campaign and presidency, Donald Trump has conflated immigration with crime. This paper, from a larger ethnographic research study, examines how students from one New Latino Diaspora high school similarly conflated deviant behavior with their peers' immigration status. Between the 2013-14 and 2014-15 school years, the number of English Learners at Springvale High School (pseudonym) more than doubled. Due in large part to a liberal (as opposed to critical) approach to multicultural education, an expectation of assimilation, and the separation of English Learners from the general education student population, misunderstandings arose and the newcomer students were widely categorized as "creeps" who "cause so many problems." The notion of White girls having to be wary of non-White "Others" illustrates how race and gender intersect, with racial difference across the lines of gender, specifically where White girls are concerned, perceived to be more problematic. K-12 schools are an important arena for #Persistence to exist, as they can either perpetuate or challenge the status quo.